The constructions of everyday ethics in Lithuanian family social work practices - Motieciene, Roberta; Laitinen, Merja; Skaffari, Pia (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in English] The aim of this study was to shed light on family social work through analyzing the insights of Lithuanian social workers about the ethical questions that emerge during their daily practices. Social workers’ ethical considerations are analyzed in the framework of “doing ethics.” Ethics work also pays attention to the broader political and social contexts behind the processes that happen within families. Our qualitative research was carried out in three of the largest Lithuanian cities: Vilnius, Kaunas and Klaipėda. Semi-structured interviews were conducted with 25 family social workers. The research findings showed that family social workers construct ethical questions through discursive themes, such as the dignity of the client and societal inequalities – especially poverty issues and social control and support. Ethical dilemmas arise in the settings where social workers do evaluations and make decisions, and where actions require professional knowledge.